Mobile application for car troubleshooting using ruled based expert system / Muhammad Faiz Mohd Nor - Mohd Nor, Muhammad Faiz (2020)
Car is one of Malaysia’s most popular and commonly used by drivers. So there are many of car problems threaten this transportation. This project aims to developing mobile awareness that can classify the type of car problem based in symptoms. The solution to the problem is a mobile diagnostic application developed and the outcome efficiently. This research has three main aims: (1) to design a rule based system based on expert domain point of view for car troubleshooting (2) to develop a prototype of car troubleshooting system (3) to test functionality of the system. The system of purpose was assessed and expertise was used for the results produced in the system. Ruled based are applied in the mobile application to treat the symptoms by using the forward chaining technique. The approach is the waterfall model used for this framework. The expected result for the program has therefore been checked by uses, whose data are obtained and which findings are matched with tests from humans’ experts. Five forms of car symptoms are running and the result is successful. Eventually the program built to incorporate a chaining technique will diagnose the car problem on the basis of the user’s symptom. The program can be improved by updating the code and adding additional types of automobiles problem for different information.